Kontribusi PERSAGI Sulawesi Barat dalam Grebek Stunting di Kabupaten Mamuju - Nurbaya Nurbaya; Agustina Uta Tabang Kalua; Muhammad Hasyim; Sri Damayanti (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
SSGI data for 2021 shows that 30.3% of under-five children are stunted in West Sulawesi. The low participation of the mothers of Mamuju Regency in Posyandu activities may be one of the factors causing the high stunting rate in West Sulawesi. The Grebek Stunting activity carried out by the District Health Office of Mamuju in collaboration with the DPD Persagi of West Sulawesi. It aimed to increase D/S coverage for toddlers as a form of early detection of stunting toddlers. This activity was carried out in four stages: preparing, refreshing anthropometric assessment, Grebek Stunting and evaluation. Grebek Stunting was carried out by visiting toddler homes to carry out anthropometric measurements and assess nutritional status. The Grebek Stunting activity involved across sectors and increased D/S coverage to 36.1% from 49.6% in July to 85.7% in August. The involvement of PERSAGI West Sulawesi and cross-sectors can increase the coverage of D/S Posyandu to increase efforts to detect early stunting in toddlers. It is suggested that policy makers can involve cross-sectors in an effort to increase community participation in Posyandu activities.